Laplacian eigenvectors and eigenvalues and almost equitable partitions - Cardoso, Domingos M.
Relations between Laplacian eigenvectors and eigenvalues and the existence of almost equitable partitions (which are generalizations of equitable partitions) are presented. Furthermore, on the basis of some properties of the adjacency eigenvectors of a graph, a necessary and sufficient condition for the graph to be primitive strongly regular is introduced. © 2006 Elsevier Ltd. All rights reserved.